Pengembangan Marker Multiepitop untuk Kit Diagnostik HPV E6 Berbasis Lateral Flow Assay melalui Pendekatan In Silico - Hasna, Nadifah; Rizki Febriyanti, Sabrina; Alginta, Taniani; Syifa Aprilia, Shafira; Fitri Sajidah, Ghaisani; Salsabila; Iin Nur Indra, Asep (Faculty of Health Science and Technology, University of Jenderal Achmad Yani, 2025)
Background : Cervical cancer is the second most common cancer after breast cancer and has a high mortality rate from all cancer deaths. Cervical cancer has been proven to be caused by continuous infection of oncogenic types of Human papillomavirus (HPV), namely high-risk HPV types including types 31, 33, 35, and 58. In the HPV life cycle, the E6 protein plays a crucial role in regulating cellular functions that contribute to cell transformation into cancer. The E6 protein from HPV types functions as the main oncoprotein that plays a role in the process of immortalization and cell malignancy. Mechanistically, the E6 protein from high-risk HPV contributes to the inactivation of the p53 tumor suppressor protein. Objective : This study aims to develop a multiepitope marker based on the E6 protein as the main component in the Lateral Flow Assay (LFA. Method : diagnostic kit with a bioinformatics approach method to identify immunogenic and conservative B cell epitopes in the HPV E6 protein which are then cloned in silico in the pET-28a (+) plasmid, so that it can produce a diagnostic kit that is specific for detecting Human papillomavirus (HPV). Result : The results showed that the designed multiepitope marker has the ability to trigger an effective immune response against B cells and has a fairly strong interaction between antigen and antibody. This study also showed the ability of the E6 protein to be expressed on the pET-28a(+) plasmid. Conclusion : This study provides a strong basis for further development and evaluation in vivo studies for the development of lateral flow assay (LFA)-based screening diagnostic kits utilizing Recombinant DNA technology.